Mediating Retinal Ganglion Cell Spike Rates Using High-Frequency Electrical Stimulation - Guo, Tianruo; Tsai, David; Yang, Chih Yu; Al Abed, Amr; Twyford, Perry; Fried, Shelley I.; Morley, John W.; Suaning, Gregg J.; Dokos, Socrates; Lovell, Nigel H. (Frontiers in Neuroscience, 2019)
Recent retinal studies have directed more attention to sophisticated stimulation strategies based on high-frequency (> 1.0 kHz) electrical stimulation (HFS). In these studies, each RGC type demonstrated a characteristic stimulus-strength-dependent response to HFS, offering the intriguing possibility of focally targeting retinal neurons to provide useful visual information by retinal prosthetics. Ionic mechanisms are known to affect the responses of electrogenic cells during electrical stimulation. However, how these mechanisms affect retinal ganglion cell (RGC) responses is not well understood at present, particularly when applying HFS. Here, we investigate this issue via an in silico model of the RGC and confirm and calibrate the model using an in vitro retinal preparation. An RGC model based on accurate biophysics and realistic representation of cell morphology, was used to investigate how RGCs respond to HFS. The model was able to closely replicate the stimulus-strength-dependent suppression of RGC action potentials observed experimentally. Our results suggest that the cellular inhibition to HFS is due to local membrane hyperpolarization caused by outward membrane currents near the stimulus electrode. In addition, the extent of HFS-induced inhibition can be largely altered by the intrinsic properties of the inward sodium current. Finally, stimulus-strength-dependent suppression can be modulated by a wide range of stimulation frequencies, under generalized electrode placement conditions. In vitro experiments verified the computational modeling data. This modeling and experimental approach can be extended to further our understanding of the effects of novel stimulus strategies by simulating RGC stimulus-response profiles over a larger range of stimulation frequencies and electrode locations than have previously been explored.